Effect of strain rates on tensile properties and fracture toughness determination of extruded Mg-Al-Zn alloys - Abdul Latif, Noradila (2015)
Extruded Mg-Al-Zn alloy is a lightweight and high strength magnesium alloy that is becoming a preferred material to be used as a structural component in automobiles. During a crash event, an automobile structure is subjected to dynamic loading. The magnesium alloy structures must be able to maintain its integrity and provide adequate protection in survivable crashes. Besides static tensile properties, tensile properties at high strain rates of extruded magnesium alloys and their fracture behaviour are some of the important parameters to be considered in design in ensuring the durability and reliability of automobile structures. In this study, the effect of strain rates on tensile properties and work hardening behaviour were evaluated for extruded Mg-Al-Zn alloys. Further, the fracture behaviour at different loading rates and the effect of temperature on fracture toughness of Mg-Al-Zn alloys were investigated. The extruded Mg-Al-Zn alloys used in this study were AZ61 and AZ31 magnesium alloys. Tensile tests under low and high strain rates were carried out using a universal testing machine and high strain rate tensile tester, respectively. The high strain rate tensile tester was designed and fabricated in-house to fulfil the requirement of tensile test under high strain rate ranging from 100 to 600 s -1 . Work hardening behaviour for low strain rate tensile specimen was determined by referring to the ASTM E646. To obtain the fracture behaviour of both alloys at different loading rates, three-point bending fracture test was conducted on pre-cracked specimens. Standard test methods i.e. ASTM E1820 and JSME S001 were referred to determine the elastic-plastic fracture toughness JIC value of AZ31 and AZ61 alloys. The JIC value obtained were then used as a standard reference value to identify a proper groove depth of a single side-grooved specimen. The side-groove depths evaluated were 25%, 35% and 50%. The proper depth of the side-grooves is confirmed after the J value obtained from the side-grooved specimen test method is identical to the JIC value that of the standard test method. The side-grooved specimen with proper groove depth was then used to determine the JIC value of AZ61 alloy at high temperature. From the results, the tensile strengths were gradually increased with increasing strain rates. However, at above 200 s-1 , the tensile strength increased significantly to more than 600 to 800 MPa. In addition, the work hardening rate for AZ61 was found higher compared to that of AZ31. Both alloys exhibited significant elastic-plastic fracture behaviour at different loading rates. It was found that 50% side-grooves depth is appropriate enough to produce valid JIC value using a single specimen. This finding is very useful especially in determining JIC value in a condition where standard multiple specimen test method is difficult to be conducted such as in high temperature environment. The JIC values of AZ31 and AZ61 at room temperature were 19 and 25 kJ/m2 , respectively. Meanwhile, the JIC value of AZ61 at 150 °C was found twice higher than the JIC value at room temperature.